Evaluación de rendimiento de quinua (chenopodium quinoa willd.) con cuatro cultivos de cobertura vegetal en el sector la Argelia cantón Loja - Amay Ortiz, José Daniel (2022)
Quinoa (Chenopodium quinoa Willd) is an Andean crop domesticated thousands of years ago by the ancient cultures of the Andean Region of South America. Its nutritional value lies in the ideal balance of amino acids in its protein, which makes it an excellent component in diets. The objective of this research was to evaluate the growth of weeds and the yield of quinoa, under four plant cover crops (CC): oats, barley, vetch and peas. The trial was established in the Quinta Experimental Docente "La Argelia” located in the city of Loja, using a completely randomized block design with 14 treatments and 3 repetitions, consisting of CCs with grass and legume species as monoculture and mixtures. Weed suppression, biomass, diversity and plant cover of weeds were evaluated. On the other hand, in the quinoa crop, the final yield of the grain and its components was evaluated. The dominant weeds were cerraja (Sonchus oleraceues) and coquito (Cyperus rotundus). The highest biomass of weeds in the phenological stages BBCH 19 and BBCH60, occurred when quinoa grew under cover crops vetch (T5), peas (T6), and peas + vetch (T12), while the lowest biomass of weeds was observed in cover crops composed of grasses (oats and barley). Weed suppression was greater in the barley + vetch (T9) treatments, as well as barley + pea + oats (T14) they exceeded 90% suppression in BBCH19, and 75% in BBCH60. On the other hand, the lowest suppression of weeds occurred in the treatments consisting of legumes such as vetch (T5), peas (T6) and peas + vetch (T12), whose lowest suppression values were close to 40%. The yield in the quinoa crop was higher in the treatments (barley + peas + oats) with 4525.6 kg. haˉ¹ T12 (vetch + pea) 3759.8 kg. haˉ¹ T5(vetch) 3085.5 kg. haˉ¹ and T1 (control without weeds) 3664.1 kg. haˉ¹. Regarding the T2 treatment (control with weeds), no results were obtained in the yield due to the interference of weeds. Therefore, the crop must remain free of weeds since it is a poor competitor of weeds to avoid yield losses. In this thesis, it is shown that the use of cover crops using grass species and their combination with legumes as predecessors of quinoa can be an alternative to improve weed management and productivity of quinoa Keywords. cover crops, weeds, quinoa